2013
DOI: 10.5958/j.0973-5674.7.2.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupressure on Labor Pain and Duration of Delivery among Laboring Women Attending Cairo University Hospital

Abstract: Background: Labor pain management continues to be a challenge for maternity nurses & physician caring for women during labor and birth process. Aim: The aim of the study was to examine the effect of acupressure at sanyinjiao point (SP6) on labor pains and the duration of delivery in primigravida women. Methods: This study was conducted at labor and delivery unit at Cairo University hospital. One hundred (100) women in labor were randomly selected (50 women for each group). Labor pain and progress were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A total of 2346 participants were involved, ranging from 60 to 213 subjects per study. Twelve (54.5%) studies recruited only the primiparous women[ 27 ],[ 28 ],[ 29 ],[ 30 ],[ 31 ],[ 32 ],[ 33 ],[ 34 ],[ 35 ],[ 36 ],[ 37 ],[ 38 ] and 10 (45.5%) studies included both primiparous and multiparous women. [ 20 ],[ 23 ],[ 24 ],[ 25 ],[ 39 ],[ 40 ],[ 41 ],[ 42 ],[ 43 ],[ 44 ] In 20 (90.9%) trials, the intervention was administered during the active phase of labor.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 2346 participants were involved, ranging from 60 to 213 subjects per study. Twelve (54.5%) studies recruited only the primiparous women[ 27 ],[ 28 ],[ 29 ],[ 30 ],[ 31 ],[ 32 ],[ 33 ],[ 34 ],[ 35 ],[ 36 ],[ 37 ],[ 38 ] and 10 (45.5%) studies included both primiparous and multiparous women. [ 20 ],[ 23 ],[ 24 ],[ 25 ],[ 39 ],[ 40 ],[ 41 ],[ 42 ],[ 43 ],[ 44 ] In 20 (90.9%) trials, the intervention was administered during the active phase of labor.…”
Section: Resultsmentioning
confidence: 99%
“…In almost all the studies, the acupressure was performed at term, except for the study by Sebastian where no details were given. [ 32 ] Twelve studies were undertaken in Iran,[ 20 ],[ 23 ],[ 24 ],[ 27 ],[ 29 ],[ 30 ],[ 31 ],[ 33 ],[ 37 ],[ 40 ],[ 41 ],[ 44 ] four studies were performed in Turkey,[ 34 ],[ 35 ],[ 36 ],[ 42 ] two studies were conducted in India,[ 28 ],[ 32 ] and a study was found for Brazil,[ 43 ] Taiwan,[ 39 ] Egypt,[ 38 ] and Korea[ 25 ] [ Table 1 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations